TEACHING READING COMPREHENSION BY USING READ-COVER-REMEMBER-RETELL (RCRR) STRATEGY TO THE EIGHTH GRADE STUDENTS AT SMP N 2 LUBUKLINGGAU - Apriliani, Tara; Hamdan; Ardayati (LP3MKIL, 2025)
This research aimed to prove that teaching reading comprehension by using Read-Cover-Remember-Retell (RCRR) strategy of recount text to eighth grade students at SMP N 2 Lubuklinggau was significantly effective. The method was used Pre-experimental design with one group pre-test and post-test. The population of this research was the eighth grade students consisted of 412 students. Simple random sampling was used and the sample selected was class VIII.2 consisted of students. The instrument was multiple choice test used to collecting the data of this research. The result showed the significant difference between the students mean score in the pre-test and post test. The average score in the pre-test was 63.94 while in the post-test was 73.15. The t-obtained was 7.54 higher than 1.688 in t-table. Therefore, the researcher found that teaching reading comprehension by using Read-Cover-Remember-Retell (RCRR) strategy to the eighth grade students of SMP N 2 Lubuklinggau was effective. Finally, that can be stated the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected.